Characteristics and outcomes of out‐of‐hospital cardiac arrest in a hilly area: Utstein Registry data from the Nagasaki Medical Region, Japan - Valeryia Zmushka; Goro Tajima; Keita Iyama; Koichi Hayakawa; Kazunori Yamashita; Takamitsu Inokuma; Hiroo Izumino; Takanobu Otaguro; Eri Uemura; Tomohiro Ueki; Shimon Murahashi; Shuhei Yamano; et al. (Acute Medicine & Surgery)
Abstract Aim To analyze characteristics and investigate prognostic indicators of out‐of‐hospital cardiac arrest (OHCA) in a hilly area in Japan. Methods A retrospective population‐based study was conducted using the Utstein Registry for 4280 OHCA patients in the Nagasaki Medical Region (NMR) registered over the 10‐year period from 2011 to 2020. The main outcome measure was a favorable cerebral performance category (CPC 1–2). Sites at which OHCA occurred were classified into “sloped places (SPs)” (not easily accessible by emergency medical services [EMS] personnel due to slopes) and “accessible places (APs)” (EMS personnel could park an ambulance close to the site). The characteristics and prognosis based on CPC were compared between SPs and APs, and multivariable analysis was performed. Results No significant improvement in prognosis occurred in the NMR from 2011 to 2020. Prognosis in SPs was significantly worse than that in APs. However, multivariable analysis did not identify SP as a prognostic indicator. The following factors were associated with survival and CPC 1–2: age group, witness status, first documented rhythm, bystander‐initiated cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) use, use of mechanical CPR (m‐CPR) device or esophageal obturator airway (EOA), and year. Both m‐CPR and EOA use were associated with a poor prognosis. Conclusion In a hilly area, OHCA patients in SPs had a worse prognosis than those in APs, but SPs was not significantly associated with prognosis by multivariable analysis. Interventions to increase bystander‐initiated CPR and AED use could potentially improve outcomes of OHCA in the NMR.